25
Пошаговое объяснение:
(из таблицы нам дано):
a · b = 112 или b = 112 ÷ a
b · c = 196 или b = 196 ÷ c
(найдем наименьший общий множитель)
112 = 2 · 2 · 2 · 2 · 7
196 = 2 · 2 · 7 · 7
общий множитель b = 2 · 2 · 7 = 28
b = 28
a = 4
c = 7
a + b - c = 4 + 28 - 7 = 25
25
Пошаговое объяснение:
(из таблицы нам дано):
a · b = 112 или b = 112 ÷ a
b · c = 196 или b = 196 ÷ c
(найдем наименьший общий множитель)
112 = 2 · 2 · 2 · 2 · 7
196 = 2 · 2 · 7 · 7
общий множитель b = 2 · 2 · 7 = 28
b = 28
a = 4
c = 7
a + b - c = 4 + 28 - 7 = 25